A Foresight Overarching Method: I. Looking for a Way to Bridge the Gap. (March 2016) - Goux-Baudiment, Fabienne
Few disciplines are as vast and diverse as that of foresight. But diversity can lead to fragmentation; to strengthen it as an asset, it is necessary that the fundamentals of its uniqueness are firmly established. Roots for this appear within several factors of oneness embedded in foresight methodological apparatus: first of them, the global toolbox that shows the transition from a research of certainty to anticipation of uncertainty and from very simple tools sketching the reality to a more subtle approach of complexity; second, are the reading grids, namely, here "foresight lens, " that generate these tools and include the worldview, the capacity for discernment, and the creation of such foresight lenses; and finally, and still upstream of paradigms, the different types of knowledge required for the practice of foresight: dynamic, systemic, epistemic, and diagnostic. Built upon these three factors, a meta-method of foresight emerges, transverse to all other methods, inclusive and enriched—not dissolved—by diversity.